A self-directed and reconstructible immobilization strategy: DNA directed immobilization of alkaline phosphatase for enzyme inhibition assays. Issue 43 (14th April 2016) - Yang, Ye; Su, Ping; Zheng, Kangle; Wang, Ting; Song, Jiayi; Yang, Yi
Abstract : A DNA-directed immobilization technique is used to develop a common method for the reversible and self-directed immobilization of enzymes. Abstract : This study focused on the development of a common method for the reversible and self-directed immobilization of enzymes based on a DNA-directed immobilization (DDI) technique. The successful anchoring of alkaline phosphatases to the surfaces of magnetic nanoparticles was confirmed using confocal laser scanning microscopy, thermogravimetric analysis and a vibrating sample magnetometer. The length of the DNA linker was optimized, with a base number of 24 providing maximum efficiency for the enzymolysis. Notably, the surface of alkaline phosphatase-functionalized magnetic nanoparticles could be regenerated using a mild dehybridization process of DNA. Furthermore, the resulting single-stranded probe DNA-modified magnetic nanoparticles could be reused to immobilize the alkaline phosphatase, which suggested that the DNA-functionalized surface of magnetic nanoparticles exhibited good reversibility. The biological activity of anchored alkaline phosphatases is evaluated in an enzyme inhibition assay. The results revealed that theophylline exhibited greater inhibitory activity thanl -phenylalanine. The proposed protocol demonstrates a simple, mild and economic pathway for fabricating enzyme modified nanomaterial and can be applied in the high-throughput screening of inhibitors.